ChemInform Abstract: Oxidative Alkenylation/Annulation of Benzimidates via Ruthenium(II)‐Catalyzed C—H Activation to Generate 3‐Methyleneisoindolin‐1‐ones. Issue 25 (5th June 2015) - Li, Xing Guang; Sun, Min; Liu, Kai; Liu, Pei Nian
Abstract: The N—H imidate group efficiently acts as a directing group in Ru‐catalyzed C—H activation allowing the regio‐ and stereoselective synthesis of methyleneisoindolinones.